Modification of silica particles with poly(phenylboronic acid) brushes for fabricating hollow mesoporous carbon nanospheres. Issue 4 (9th November 2022) - Li, Die; Hong, Mei; Wang, Yan; Bao, Chunyang; Xu, Xiaoling; Chen, Jing; Peng, Bin; Zhang, Jingyu; Wang, Bingyu; Zhang, Qiang
Abstract: Porous carbon nanospheres have attracted extensive attention due to their excellent advantages in specific surface area, pore distribution, and electronic conductivity. Herein, boron‐doped hollow carbon nanospheres with mesoporous walls have been successfully synthesized via a combination of hard/soft templating and boronic acid/sugar ligation. Surface‐initiated Cu(0) mediated reversible deactivation radical polymerization was used to initiate the polymerization of 2‐hydroxyethyl acrylate and poly(ethylene glycol) methyl ether acrylate from the surface of silica. 4‐carboxy‐3‐fluorophenylboronic acid was introduced as a boron precursor by N ‐(3‐dimethylaminopropyl)‐ N ′‐ethylcarbodiimide hydrochloride coupling and fructose was introduced as a carbon precursor by boronic esters. After carbonization and template etching, boron‐doped porous carbon spheres could be obtained. We believe such in‐situ heteroatom‐doped method has great potential in preparing hollow mesoporous carbon nanospheres with excellent properties. Abstract :